The Influence of Event Marketing Factors on Visit Interest at the Skafourta Expo 2025 Event in Yogyakarta - Nining Yuniati; Rina Kuswardani (CV. Ulil Albab Corp, 2025)
The event will be considered successful if it attracts a large number of visitors. Among the ways to promote an event so that it becomes widely known to potential audiences is by marketing the event using factors that have been proven according to empirical facts in a number of event cases. These factors are entertainment, excitement, enterprise, and price. Through these factors, this research will prove whether they also influence visitor enthusiasm for the Skafourta event, which is a flagship event for middle-class (SMK) education in Yogyakarta. The sample taken was 317 respondents, selected using a random method. Multiple regression analysis showed that the factors of entertainment, excitement, enterprise, and price, both individually and collectively, significantly influence event visitor motivation